Strategi Mitigasi Pembiayaan Bermasalah pada BSI RFO Medan - Mahvi, Muhammad Rizky; Siregar, Muhammad Habibi (Jurnal EMT KITA, 2025)
This study aims to explore and analyze the non-performing financing mitigation strategies implemented by Bank Syariah Indonesia (BSI) Regional Finance Office (RFO) Medan. Using qualitative methods and case study approaches, this study explores the experiences and mitigation practices carried out by BSI management in handling non-performing financing. The data was obtained through in-depth interviews with managers and relevant officers at BSI RFO Medan as well as analysis of relevant documents. The main findings show that BSI RFO Medan implements various mitigation strategies which include financing restructuring efforts, stricter monitoring, and a personal approach with customers. However, challenges such as inconsistencies between the bank's internal policies and external conditions, as well as the low level of customer understanding of sharia financing, are obstacles to the effectiveness of the strategy. This study recommends the need to increase education to customers, improve the monitoring system, and strengthen communication between banks and customers to reduce the potential for non-performing financing in the future.